2015
DOI: 10.1088/0029-5515/56/1/016012
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles of shear flow in nonlinear multi-scale interactions

Abstract: Effect of shear flow on the multi-scale nonlinear interaction in plasmas is numerically investigated by using a self-consistent Landau-fluid model. Dual roles of shear flow in the process are discovered, significantly suppressing micro-scale fluctuations and dramatically promoting macro-scale fluctuations. Furthermore, its similar dual roles in turbulent transport are also demonstrated. The novel underlying mechanism for the nonlinear promotion is identified as the formation of a large vortex flow inside magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…The poloidal flow can be important as it will be discussed in next section. In fact, the poloidal shift of the turbulence with respect to the X-point coincides with the direction of the local poloidal flow [9,27,29]. This locality of the island-associated T e turbulence is consistently observed in other experiment [43].…”
Section: The T E Turbulence and Its Characteristicssupporting
confidence: 81%
“…The poloidal flow can be important as it will be discussed in next section. In fact, the poloidal shift of the turbulence with respect to the X-point coincides with the direction of the local poloidal flow [9,27,29]. This locality of the island-associated T e turbulence is consistently observed in other experiment [43].…”
Section: The T E Turbulence and Its Characteristicssupporting
confidence: 81%
“…Measurements of the low- k T e turbulence and the flow shear around an MI in KSTAR experiments revealed that the turbulence is nonlinearly regulated by the flow shear development around the MI and localized to the small region near the X-point. These spatial patterns of the turbulence and the shear flow are in broad agreement with the results from many fluid and gyrokinetic simulations 15 , 16 , 19 , 20 , 22 , 23 . In particular, ref.…”
Section: Discussionsupporting
confidence: 88%
“…Though it is not shown in this paper, the flow shearing rate across the MI is also sufficiently large (ω E×B ≥ 1.0 × 10 5 [1/s]) to prevent the increased turbulence near the X-point from spreading into the MI in this case [10]. Note that these spatial patterns of the turbulence and the shear flow are in qualitative agreements with the outcomes of the fluid and gyrokinetic simulations [17,18,21,22,24,25].…”
Section: Inhomogeneous Low-k T E Turbulencesupporting
confidence: 68%
“…Recent tokamak experiments [5,6,7,8,9,10,11,12,13,14,15] and simulations [16,17,18,19,20,21,22,23,24,25,26] found that the MI affects the evolution of the ambient broadband fluctuations (or simply referred as 'plasma turbulence' [27]). Plasma turbulence is significantly altered by the MI itself or a modification of the equilibrium profiles due to its presence.…”
mentioning
confidence: 99%